Efektivitas Penggunaan Aplikasi Pamitabara Terhadap Kegunaan, Kemudahan, dan Tindakan Remaja Mengonsumsi Tablet Tambah Darah Di Kabupaten Cirebon - Whinalda, Dhinda; Herawati, Yanti; Sugih, Siti (Jurnal Kebidanan Malakbi, 2025)
The prevalence ofianemiaiin Puskesmas Ciroyom 13,14% with approximately 21 million adolescent girls. Problems related to compliance are a major obstacle in daily iron supplementation. Providing counseling or health education can use several media, one of which is the digital media application “Pamitabara”. Theipurpose ofithis study wasito analyzeithe effectivenessiiof usingiithe application of obedient drinking blood tablets (“Pamitabara”) on the usefulness, convenience, and action of adolescents in taking blood tablets in the Waruroyom Puskesmas Working Area, Cirebon Regency. Cross sectional research method with pretestiandiposttestidesign. iTheistudy was conductedion 60 adolescent girls who were taken from 3 schools by lottery. Sampling using purposive sampling. Data analysis usingipairedit-test andiN-Gain test. iThe resultsishowed thatiin the interventionigroup givenithe “Pamitabara” application, almost all respondents were compliant with taking blood supplement tablets and in the control group given nutrition cards, almost three-quarters of respondents were not compliant. Then, almost all respondents stated that it wasieasy toiuse thei “Pamitabara” application and the “Pamitabara” application was very useful in helping take blood supplement tablets. The effectiveness test of the “Pamitabara” application and nutrition cards found that the “Pamitabara” applicationiwas quite effective in increasing adolescents taking blood tablets, while the nutrition cards were less effective. In conclusion, the “Pamitabara” application is effective on the usefulness, convenience, and action of adolescents in consumingiblood supplementitablets. It isiihoped that young women will use the "Pamitabara" application as an educational medium and a fertile period for increasing hemoglobin, especially for young women who have anemia.